Uang dan “Ayunan” dalam “Etnik Melayu” - Zeny Novita Marpaung; Yummy Jumiati Marsa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study describes the value of money in the Malay children's swing tradition.This swing remains a Malay tradition to this day. In this study, researchers discovered the problem of the relationship between the value of money and the swinging tradition of the Malay people. The purpose of this study is to describe that parents prioritize their children's education and continue the tradition of rocking their children when they have grown up and the parents have enough finances, which is characteristic of the Ma ethnic group. Lai with the value of money in the lives of Malays, they can ensure the education of children and carry out the swinging process at any time, while maintaining the cultural value of carrying out the traditions tradition among the Malay community, especially in Sukarame village, Kualuh Hulu district, Labuhan Batu North Regent. The method used in this study is a qualitative method using descriptive analysis. The data collection techniques in this study were observation, interviewing, and note-taking. During the procession, the Malay tradition of swinging children is carried out in a series of events. The sequence begins with Barzanji, where a child swings on a rope, along with Marhaban, distributes flour, distributes potpourri flowers to those who have come to attend the event and ends with a prayer.